Therapeutic Potential of Gene-Modified Regulatory T Cells: From Bench to Bedside - Chae, Wook-Jin; Bothwell, Alfred L. M. (Frontiers in Immunology, 2018)
Regulatory T cells (Tregs) are an important subset of adaptive immune cells and control immune reactions for maintaining homeostasis. Tregs are generated upon their encounter with self or non-self-antigen and mediate tolerance or suppress aberrant immune responses. A high level of specificity of Tregs to recognize antigen(s) suggested their instrumental potential to treat various inflammatory diseases. This review will first introduce seminal basic research findings in the field of Tregs over the last two decades pertinent to therapeutic approaches in progress. We will then discuss the previous approaches to use Tregs for therapeutic purposes and the more recent development of gene-modification approaches. The suppressive function of Tregs has been studied intensively in clinical settings, including cancer, autoimmunity and allotransplantation. In cancer, Tregs are often aberrantly increased in their number and their suppressor function inhibits mounting of effective anti-tumor immune responses. We will examine potential approaches of using gene-modified Tregs to treat cancer. In autoimmunity and allotransplantation, chronic inflammation due to inherent genetic defects in the immune system or mismatch between organ donor and recipient results in dysfunction of Tregs, leading to inflammatory diseases or rejection, respectively. Since the recognition of antigen is a central part in Treg function and their therapeutic use, the modulation of T cell receptor specificity will be discussed. Finally, we will focus on future novel strategies employing the therapeutic potential of Tregs using gene modification to broaden our perspective.